Effect of barley replacement by acorns (Quercus coccifera L.) as energy supplement on in vitro fermentation - Moujahed N.; Ben Mustapha C.; Kayouli C. (Advanced nutrition and feeding strategies to improve sheep and goat, 2007)
The effect of barley replacement by acorns of kermes oak on in vitro gas production, using vetchoat hay basal diet, was studied. Control diet (D0) was composed of a mixture of oat-vetch hay and barley grains (2/3 and 1/3 respectively). Experimental diets included increased proportions of acorns (A) replacing barley (B) in the concentrate part of D0, on DM basis (D1: 25% A, 75% B; D2: 50% A, 50% B; D3: 75% A, 25% B; D4: 100% A). For all diets, kinetic of in vitro gas production was determined in 100 ml graduated glass syringes with inocula from fistulated goats. All diets were low in crude protein (6.5 to 8.3% DM, respectively in D3 and D0) and moderate in lignocellulose (ADF) (19.5 to 22.7% DM, respectively in D0 and D4). Acorns are lower in metabolisable energy (1767 kcal kg-1 DM) than barley (2484 kcal kg-1 DM). Diets 0, D1 and D2 exhibited similar total gas production (69.3 ml on average). Diet 3 and D4 produced similar amounts of gas (65.4 ml), significantly (P<0.01) lower than D0, D1 and D2. The rate of gas production values ranged from 0.057 (D4) to 0.062 h-1 (D2). It was concluded that acorns could replace no more than 50% of the amount of barley grains in the concentrate used in this experiment otherwise a decrease of the in vitro gas production, thus of microbial activity is expected.
11. Seminar of the FAO-CIHEAM Sub-Network on Sheep and Goat Nutrition, 2005/09/08-10, Catania (Italy)